The expression of human leukocyte antigen by human ejaculated spermatozoa - Sereshki, Nasrin (Mol Genet Genomic Med, 2019)
BACKGROUND: After coitus and insemination, an inflammatory response is evident in the female reproductive tract (FRT). Semen contains a variety of immune‐activating components that have a major role in the induction of an immune response in the FRT. One of the most important is (human leukocyte antigen) HLA molecules which are present in soluble form in seminal plasma and in membrane form on the surface of cells (such as epithelial and leukocytes) existing in semen. Nevertheless, there is considerable debate over the expression of HLA antigens by human spermatozoa. Considering the critical role of HLA molecules in reproduction and the induction of an immune response, it is very important to clearly define HLA expression by spermatozoa and the role of these molecules in sperm morphology, motility, and strength to fertilize an egg. Therefore, the objective of this study was to determine HLA expression by ejaculated spermatozoa. The results of this study will facilitate the design of future studies. METHOD: Semen samples were collected from 50 healthy men with normal semen status by masturbation after 2–3 days of sexual abstinence. After purification of normal spermatozoa, HLA class I & II expression was evaluated by quantitative real‐time PCR and flow cytometry methods. RESULTS: The results showed the expression of both HLA class I & class II by spermatozoa. The results also showed that the expression of HLA class Ⅱ was significantly more than HLA class Ⅰ. CONCLUSION: Spermatozoa express both HLA class I & class II molecules.